GIZI SEHAT MENGHADAPI MENOPOUSE - Uliyatul Laili; Yati Isnaini Safitri; Rizki Amalia; Fathimah Zahra (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Menopause is one of the stages in a woman's life cycle where there are physiological and psychological changes. A person's nutritional status is not formed instantly in a person. So it is necessary to establish as early as possible to get maximum conditions in dealing with every phase of a woman's life. This service program aims to improve the nutritional status of Islamic boarding schools through the formation of a nutrition team and the preparation of a nutritional menu table as a daily menu. This service activity begins with coordinating and outreach to female students and boarding school administrators. Furthermore, an assessment of the food menu has been carried out in Islamic boarding schools, and continued with the preparation of food menu adjustments with balanced nutrition. The results of community service activities in the form of counseling showed that there was a significant increase in the knowledge of students and boarding school administrators about nutritional needs. This increase in knowledge encourages students and administrators to start paying attention to the preparation of daily menus in accordance with the needs of nutritional standards. So it is hoped that healthy nutritional status has begun to form from adolescence, late adulthood and in the end it will be useful in dealing with the life cycle of women during menopause where there will be many changes in the body system.